Impact and Adaptability of Conventional Blended Learning Strategies in Enhancing Student Motivation a Qualitative Investigation of Unplugged Pedagogy in Boarding Schools with Restricted IT Facilities - Sismala Harningtyas; Fahmiya Azlin (CV. Get Press Indonesia, 2026)
This research investigates the conflict between the Merdeka Curriculum's goal of learner autonomy and the strict device-free policies of military-based schools facing severe ICT scarcity. Utilizing an instrumental qualitative case study, the study reveals an asymmetrical blended model, or unplugged pedagogy, centered on intensive analog instruction and strategically restricted IT use (Hadi & Anwar, 2025; Husen et al., 2025). While this model successfully promotes cognitive focus and fulfills needs for competence and relatedness (Ryan & Deci, 2020), the resulting constraint on informational access severely limits autonomy, generating a critical pedagogical paradox (Maufiroh et al., 2025). The findings underscore teaching resilience (Syarifuddin & Saparuddin, 2021) and mandate policy reform to balance security with controlled ICT access, providing a vital blueprint for resource-constrained contexts like Indonesia's 3T regions (Rasheed et al., 2020).